Knowledge and attitudes of Australian livestock producers concerning biosecurity practices. Issue 11 (4th August 2020) - Paquette, CC; Schemann, KA; Ward, MP
Abstract : Biosecurity risks are a major threat to the profitability of the industry as well as impacting human and animal health. Livestock producers play a crucial role in biosecurity as the first to notice changes in the health or productivity of their stock and are generally responsible for implementing protective measures. However, uptake of biosecurity measures by producers is variable. We critically appraised the current literature regarding biosecurity practices in Australian livestock industries and highlight aspects that are well understood as well as those where further research or information is needed. Findings from 12 cross‐sectional studies suggest that Australian producers' knowledge of biosecurity methods and importance might have a positive influence on their willingness to implement or incorporate biosecurity practices. There is moderate evidence supportive of biosecurity being well understood by livestock producers across Australia. Barriers to producers using biosecurity practices included lack of information or communication from agricultural, veterinary or government organisations. It was found that larger stock numbers were positively correlated with biosecurity implementation and that producers used veterinarians, government and industry agencies as resources for trusted information.